2014
DOI: 10.1097/01.aud.0000439101.07257.ed
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Impairments in HIV-Infected Individuals in Tanzania

Abstract: Objectives Abnormal hearing tests have been noted in HIV-infected patients in several studies, but the nature of the hearing deficit has not been clearly defined. We performed a cross-sectional study of both HIV+ and HIV− individuals in Tanzania using an audiological test battery. We hypothesized that HIV+ adults would have a higher prevalence of abnormal central and peripheral hearing test results compared to HIV− controls. Additionally, we anticipated that the prevalence of abnormal hearing assessments would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(94 citation statements)
references
References 21 publications
(27 reference statements)
6
86
2
Order By: Relevance
“…In our study with 449 HIV+ adults no differences in threshold audiometry were seen between the HIV+ and HIV− groups (Maro et al 2014). Luque et al (Luque et al 2014) also showed no major differences in audiometric thresholds between HIV+ and HIV− adults in the their study of 278 HIV+ adults.…”
Section: Introductioncontrasting
confidence: 48%
See 3 more Smart Citations
“…In our study with 449 HIV+ adults no differences in threshold audiometry were seen between the HIV+ and HIV− groups (Maro et al 2014). Luque et al (Luque et al 2014) also showed no major differences in audiometric thresholds between HIV+ and HIV− adults in the their study of 278 HIV+ adults.…”
Section: Introductioncontrasting
confidence: 48%
“…The testing system has been described in a previous publication from our group (Maro et al 2014). The laptop-based hearing testing system included: (a) a questionnaire administered to gather data on self-reported hearing and exposure to noise, drugs and toxins, (b) tympanometry to assess middle ear function, (c) threshold audiometry (either Békésy or a modified Hughson-Westlake protocol) to measure hearing sensitivity, and (d) distortion product otoacoustic emission (DPOAE) testing to assess cochlear function.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that HIV infection or its treatment could be a possible cause of difficulty in perceiving sounds with relatively normal audiometry [8] . A case report in 2004 reported a patient who sustained a significant head injury and was complaining of difficulties in listening, paying attention, and communicating [9] .…”
Section: Current Proposed Classification Of Apdmentioning
confidence: 99%